MODEL PENINGKATAN PRODUK BERBASIS RAMAH LINGKUNGAN - Sri Rahayu; Nabila Kharimah Vedy; Evi Novitasari (Jurnal Signaling, 2023)
Environmentally friendly advertising (green advertising) is one of the strategies used by companies in carrying out environmentally friendly marketing. Green advertising is considered an important factor for increasing the intention of environmentally friendly products. But on the other hand, there is previous research which found environmentally-friendly advertising had no role in increasing green purchase intentions. This difference is a research gap that must find a solution to cover the gap. The aim of this research is to find a solution for the research gap between green advertising and purchase intention of environmentally friendly products with environmental knowledge as a mediating variable. Based on previous research studies, stated that environmentally friendly advertising can increase environmental knowledge. Furthermore, environmental knowledge plays an important role in increasing the purchase intention of environmentally friendly products. In other words, environmentally friendly advertising can increase the purchase intention of environmentally friendly products, either directly or indirectly through environmental knowledge. Based on this, a conceptual model can be built to research the purchase intention of environmentally friendly products